The Impact of Multi-Stage Discussions Using Google Classroom and WhatsApp on Higher Order Thinking Skills in Learning Newton's Law of Gravity - Zainah, Rohantika (Jurnal Pembelajaran Fisika, 2024)
Online learning utilizes internet networks to provide accessibility, connectivity, and flexibility. One innovative approach is employing multi-stage discussion learning models through platforms like Google Classroom and WhatsApp. This model is particularly effective in enhancing students' higher-order thinking skills (HOTS). This study investigates the impact of implementing multi-stage discussions using Google Classroom and WhatsApp on the HOTS of 10th-grade students studying Newton's Law of Gravity at SMAN 1 Tanjung Raja. The research adopts a quasi-experimental method with a matching-only posttest control group design, involving 35 students in the experimental class and 36 students in the control class over three sessions for each class. Pretest results showed a similar baseline between the two classes, with a difference of 9.1%. However, post-test results revealed a 15.9% difference, with the control class improving by 16.5% and the experimental class by 41.5%. The N-gain scores were 0.42 for the control class and 0.54 for the experimental class, both in the moderate category. Normality tests indicated that all data were normally distributed (p > 0.05), and homogeneity tests showed no significant difference (p = 0.264). The independent t-test hypothesis test revealed a significant effect (p < 0.05) with tcount 97.158 > ttable 1.995, indicating that the multi-stage discussion model using Google Classroom and WhatsApp significantly influences the learning process and enhances HOTS. These findings suggest that integrating digital platforms in learning can effectively improve students' critical thinking and problem-solving abilities.Keywords: Google Classroom, higher order thinking skills, Newton's Laws, multi-stage discussion, WhatsAppDOI: http://dx.doi.org/10.23960/jpf.v12.n1.202403